Les mobilités spatiales féminines entre logiques individuelle et familiale - Sihé Néya (EchoGéo)
The mobility spaces of burkinabe women migrants between Burkina Faso and Côte d’Ivoire are not confined to their family’s place of residence. This paper, based on data collected in Burkina Faso and Côte d’Ivoire, investigates the relationship to spatial mobility of Burkinabe women returning from Côte d’Ivoire to their country of origin, Burkina Faso. It argues that the return to Burkina Faso of Burkinabe women coming from Côte d’Ivoire cannot be explained solely as a family strategy. They practice multiple forms of mobility, which are driven by precarious life situations but also by the desire and need for material and financial autonomy.